Oil palm empty fruit bunch biochar fertilizer as a solution to increasing the fertility of peat soil for sustainable agriculture - Sri Nuryani Hidayah Utami; Uray Suci Yulies Vitri Indrawati (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Utilization of waste oil palm empty fruit bunches as an ameliorant in the form of biochar enriched with chicken manure and urea fertilizer to increase the fertility of immature (seedling) oil palm planted on peat soil which has poor soil physical, chemical, and biological characteristics. Methods: Biochar material, namely empty fruit bunches, was subjected to conventional pyrolysis for 3, 4 and 5 hours at a temperature of 400°C. Then the biochar is weighed to get the desired proportion of biochar then sieved through a 60 mesh sieve.nd analyzed for pH, ash content, organic-C, total-N, total-P, total-K, as well as biochar functional groups using Fourier Transform Infrared Spectroscopy (FTIR), and structural analysis using Scanning Electron Microscopy (SEM). The implementation of the research consisted of 2 activities, namely 1) Planting oil palm seedlings in polybags by giving treatment according to the dose and 2) Chemical characterization of biochar, peat soil properties and growth and NPK uptake of oil palm seedlings. Results: Bs1 treatment: (Biochar oil palm empty fruit bunches: chicken manure:urea by (280g:555g:90g) increased plant height to 213%, 36% number of leaves, 49.7% soil total N, 16.2% available P, and 35% available K compared to control. Conclusion: Palm oil waste in the form of empty bunches of biochar, has special properties such as porous structure, relatively large surface area with various functional groups, hence it has the potential as an ameliorant to increase marginal soil fertility including peat and increase plant growth of oil palm seedlings.